Seaweed Cultivation to Increase Community Economic Income from an Islamic Economic Perspective (Case Study in Langgudu District, Rompo Village) - Dian Wulandari; Muhammad Rasyad Al Fajar; Muhammad Zia Ulhaq (JURNAL ECONOMINA, 2026)
This study was conducted to examine the role of seaweed farming in increasing community income and to analyze its implementation based on the principles of Islamic economics in Rompo Village, Langgudu Subdistrict, Bima Regency. This study employed a qualitative approach using field research methods. Data collection was conducted through observation, in-depth interviews, and documentation. The findings reveal that seaweed farming activities in Rompo Village are carried out through a series of processes that integrate local community knowledge with the involvement of family labor. This enterprise makes a tangible contribution to the household economies of the farmers, with net income ranging from Rp400,000 to Rp1,500,000 per production cycle. The income earned is primarily allocated to meet basic family needs, education expenses, and healthcare costs. From an Islamic economic perspective, the production and trade of seaweed have embodied the values of honesty, justice, cooperation, and responsibility. Nevertheless, transparency in pricing and the financing system still needs to be strengthened to prevent inequality while ensuring the sustainability of the business in accordance with Sharia principles.